Pengaruh Penambahan Pati Talas (Colocasia esculenta) sebagai Stabilizer terhadap Viskositas dan Uji Organoleptik Yogurt - Aju Tjatur Nugroho Krisnaningsih; Tri Ida Wahyu Kustyorini; Magdalena Meo (Fakultas Peternakan, Universitas PGRI Kanjuruhan Malang, 2020)
The aim of this research was to know effect of adding the taro starch (Colocasia esculenta) as a stabilizer on viscosity and organoleptik test. The research method used was a laboratory experiment using a completely randomized desing (CRD), which consists of 4 treatments (P0= without the addition of taro starch, P1= addition of taro starch 0,5%, P2= addition of taro starch 1%, P3= addition of taro starch 1,5%) and 3 replications, then continued by Least Significant Difference (LSD). The result showed that the addition of taro starch as a stabilizer provides highly significant effect (P< 0,01) on the viscosity and texture yogurt. Result showed the highest viscosity values by adding starch 1,5%=8230 cP and the lowest score without the addition of starch is 0%=830 cP. An texture of yogurt on the highest volue with the addition of taro starch 1,5% with a score of 9 and the lowest rate of 0% was 6,8. While adding starch not have the effect of (P>0,05) in color, taste and flavor. The highest score is of a favorite by adding starch 0,5% = 7,4 and the lowest 1% =7,0. Favorit yogurt on the highest score is adding starch 0,5% = 6,47 and the lowest 1,5% =5,53. On fondnes scent highest score by adding starch 0% and 0,5% =7,4 and the lowest value adding starch 1% and 1,5% =7,3. It was concluded that the addition of taro starch as a stabilizer of 1.5% produces yogurt optimum quality in terms of viscosity and texture of yogurt.